2010
DOI: 10.1002/humu.21187
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and clinical analysis ofRAF1in Noonan syndrome and related disorders: dephosphorylation of serine 259 as the essential mechanism for mutant activation

Abstract: Noonan syndrome (NS) and related disorders are autosomal dominant disorders characterized by heart defects, facial dysmorphism, ectodermal abnormalities, and mental retardation. The dysregulation of the RAS/MAPK pathway appears to be a common molecular pathogenesis of these disorders: mutations in PTPN11, KRAS, and SOS1 have been identified in patients with NS, those in KRAS, BRAF, MAP2K1, and MAP2K2 in patients with CFC syndrome, and those in HRAS mutations in Costello syndrome patients. Recently, mutations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
124
1
9

Year Published

2011
2011
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(146 citation statements)
references
References 35 publications
12
124
1
9
Order By: Relevance
“…In this study, the authors also observed that individuals with BRAF mutations, similarly to those mutated in SOS1, have better preserved postnatal growth compared with patients harboring other genotypes [14]. In contrast, short stature seems to be more frequently associated with mutations of RAF1 (mean height SDS of -0.5±0.9 SDS compared to NS standards) or SHOC2 (-1.3±0.7) [14,20,21]. Nonetheless, it must be emphasized that these reports did not take into account a large number of patients, notably in the case of subjects with rare genotypes (e.g., SHOC2 mutations).…”
Section: Influence Of Genotype On Spontaneous Growth In Subjects With Nssupporting
confidence: 56%
“…In this study, the authors also observed that individuals with BRAF mutations, similarly to those mutated in SOS1, have better preserved postnatal growth compared with patients harboring other genotypes [14]. In contrast, short stature seems to be more frequently associated with mutations of RAF1 (mean height SDS of -0.5±0.9 SDS compared to NS standards) or SHOC2 (-1.3±0.7) [14,20,21]. Nonetheless, it must be emphasized that these reports did not take into account a large number of patients, notably in the case of subjects with rare genotypes (e.g., SHOC2 mutations).…”
Section: Influence Of Genotype On Spontaneous Growth In Subjects With Nssupporting
confidence: 56%
“…Among Costello syndrome patients with a cardiovascular problem, the frequent occurrence of arrhythmia (65% this study, 45% in literature review) is striking. Only patients with a RAF1 mutation approach this in overall frequency (13% among all patients), or with any atrial tachycardia (31%), one of whom had EAT [Kobayashi et al, 2010]. The finding of an abnormal electrocardiogram with conduction abnormalities in Noonan syndrome with multiple lentigines syndrome is well-described (45% reporting patients) and is not compared to patients with non-reentrant atrial tachycardia.…”
Section: Comparison With Rasopathiesmentioning
confidence: 99%
“…suggests that severe subaortic obstruction requiring surgical treatment is more frequent in Costello syndrome than in Noonan or CFC. HCM due to RAF1 mutations [Kobayashi et al, 2010] and in Noonan syndrome with multiple lentigines [Limongelli et al, 2007] is often severe, and longitudinal studies are needed to delineate a comparison to Costello syndrome. The resolution by echocardiographic criteria of HCM in five patients with Costello syndrome is not unique among RASopathies, and requires monitoring across the spectrum of RASopathies in longitudinal studies.…”
Section: Comparison To Other Rasopathiesmentioning
confidence: 99%
“…RAS activation results in the stimulation of RAF family members, which have been implicated in the development of hypertrophy (56,57) and of HCM in RASopathies (9,13,14). RAF1 mutations have been more frequently found to be associated with HCM, and nearly all NS patients with RAF1 mutations exhibit HCM (58). Like NS patients, mice heterozygous for the NS-associated RAF1 mutation exhibit eccentric cardiac hypertrophy (59).…”
Section: Pathophysiological Signaling: Experimental Relevance Of the mentioning
confidence: 99%